Infusion administration billing for vedolizumab and infliximab in inflammatory bowel disease. (2nd November 2018) - Null, Kyle; Kumar, Varun; Lissoos, Trevor; Luo, Michelle
Abstract: Aims: Increasing use of biologics has led to interest in treatment components with potential for cost savings. This study was aimed at comparing administration times and associated costs of infliximab and vedolizumab infusions for inflammatory bowel disease (IBD). Materials and methods: This study used claims data from the Symphony Health Integrated Dataverse to identify IBD patients using infliximab or vedolizumab between 20 May 2014 and 29 February 2016. Use of Current Procedural Terminology administration codes was evaluated and costs calculated using the 2016 Center for Medicare and Medicaid Services Physician Fee Schedule. Assessments included infusion times, associated costs, productivity loss using average wage estimates from the United States Bureau of Labor Statistics, and home infusion adoption. Results: A total of 10, 051 infliximab and 3114 vedolizumab patients with first-hour claims were identified; 52.0% were female and 64.5% had Crohn's disease. There were 48, 377 infliximab first-hour claims (mean 4.8 infusions per patient); 46, 462 (96.0%) had a second-hour claim. In comparison, there were 14, 717 vedolizumab claims (mean 4.7 infusions per patient), with only 411 (2.8%) second-hour claims, resulting in vedolizumab cost savings of approximately $1.27 million. The difference in second-hour infusions resulted in 46, 051 additional hours of productivity loss with infliximab, and lost wages averaging $1.18 million (range $0.68–$1.77 million). Limitations: Administration costs were inferred as charge costs and not directly assessed. Productivity loss assessed time spent on infusion only, and included a small proportion of patients beyond working age. Conclusions: Second-hour infusion billing was significantly lower with vedolizumab than with infliximab, corresponding to cost savings and reduced productivity loss.